Study on corrosion kinetics of 310H in different simulated MSW combustion environment. The influence of SO2 and H2O on NaCl assisted corrosion. (1st July 2019) - Wenga, Terrence; Chen, Guanyi; Ma, Wenchao; Yan, Beibei
Highlights: The corrosion kinetics and corrosion rate was determined. The effect of NaCl, H2 O vapor, and SO2 on corrosion of 310H was studied. The corrosive contribution was in the order: NaCl > H2 O vapor > SO2 . Corrosion mechanisms in different environment along with time were discussed. Abstract: In this study, the corrosion kinetics of alloy 310H with and without each of NaCl, H2 O-vapor, and SO2 under an oxidizing environment at 500 °C was investigated and the corrosion characteristics in each exposure were compared. The contribution of NaCl, H2 O, and SO2 to the corrosion rate was calculated and the corrosion mechanisms in each condition were characterized by means of ex-situ and in-situ thermogravimetric mass-gain measurements, SEM/EDS, XRD, XPS, and theoretical calculations. The contribution was in the order of NaCl>H2 O > SO2 . Corrosion was linear in the absence of SO2 while in the absence of NaCl, corrosion displayed a multi-stage behavior.